Interim findings on universal access to information and communication technologies the cases of Carmona and Puerto Princesa - Alampay, Erwin Gaspar A. (Philippine Journal of Public Administration, 2006)
The age of information and communication technology (ICT) has brought new trends in delivering public services. ICT has provided more possibilities for reaching and communicating with people and has brought variety of ways in availing of services such as the use of short message services (SMS) and the Internet. With the liberation of ICT in today's society, this article attempts to look at how these technologies have affected the lives of the ordinary people in accessing ICT and assess whether everybody even the long disadvantaged would finally gain access to information and new knowledge. This article presents the results of a survey in Carmona, Cavite and Puerto Princesa City, Palawan and reveals that even with liberalization in communications industry, universal access is one important area that will remain under government regulation. For everyone in societyto have equal opportunities to the use of ICT, the author suggests that strategies must go beyond access in terms of proximity to the ICT infrastructure, but also look into the socioeconmic and cultural barriers to its use.